How to Protect Your Dental Practice from Unwarranted Intrusions - Duane Schmidt (Wolters Kluwer Medknow Publications, 2011)
Risk management is the study and practice of how to avoid liti-gious perils in dental practice. All too often risk management is shunted to a minor role in the frenzy of the today's dental schools as they strive to graduate capable dentists. A sophisticated office risk management program can boast high rewards while minimizing risks in a dental practice.The genesis of this article is hinged on fifty years of dental practice, fourteen in the specialty of pediatric dentistry and the remainder in a large general practice (34 chairs, 55 employees, ten hygienists and seeing 200 patients daily and 400 new patients monthly). A practitioner can learn many key lessons in risk management when encountering so many patients and staff.What I learned was how to avoid the pitfalls, especially those perils springing from five sources: poorly informed patients, displeased patients, patients who owe you payment, dissatisfied (usually former) staff members and patients whom you have let the settlement scheme drag untowardly. This paper outlines seven specific and proven risk management strategies to minimize these perils.